NEW APPROACH TO TREATMENT OF ONCOLOGICAL DISEASES - V.G. Dorofeichuk; P.P. Potekhin; S.A. Sher (Union of pediatricians of Russia, 2010)
Oncological diseases are the second leading cause of deaths. Immune system disorders and enzymatic imbalances undoubtedly play a role in the development of tumors. Despite the multifactorial nature of oncological pathology development, endogenous lysozyme deficiency is an important condition of a disease nosogenesis. The article provides a theoretical and experimental validation for the use of lysozyme and antioxidant agents as an alternative therapy for oncological diseases. Key words: oncological diseases, lycozyme, isoantigens, muramine, free radicals. (Pediatric Pharmacology. - 2010; 7(4):37-39)